Influence of Workforce Qualification on Service Level in a Flow Shop with two Lines. Issue 13 (2019) - Schober, Andreas; Altendorfer, Klaus; Karder, Johannes; Beham, Andreas
Abstract: Finding the optimal workforce qualification is important in many different industries. Cross-qualifications play an important role if workers are required to perform various tasks during working hours. This is especially crucial in production plants where workforce has to be trained to operate multiple machines throughout the day, and is closely connected to staff planning and job scheduling. In this paper, a flow shop system consisting of two lines is used to analyse various predefined workforce qualification profiles. To measure the performance, a simulation model is applied where the sum of qualifications is compared with the achieved service levels. Scenarios that differ in the number of available workers as well as the amount of transition times needed by workers to switch between stations and lines are analysed. Furthermore, multi-objective simulation-based optimization is conducted in order to find improved qualification profiles. The achieved results from both, the predefined and the optimized qualification profiles, are promising and managerial insight is gained for future research in this domain.